2023
DOI: 10.3390/s23083943
|View full text |Cite
|
Sign up to set email alerts
|

A New Design to Rayleigh Wave EMAT Based on Spatial Pulse Compression

Abstract: The main disadvantage of the electromagnetic acoustic transducer (EMAT) is low energy-conversion efficiency and low signal-to-noise ratio (SNR). This problem can be improved by pulse compression technology in the time domain. In this paper, a new coil structure with unequal spacing was proposed for a Rayleigh wave EMAT (RW-EMAT) to replace the conventional meander line coil with equal spacing, which allows the signal to be compressed in the spatial domain. Linear and nonlinear wavelength modulations were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When the receiver is a spatial matched filter, spatial pulse compression (SPC) can be realized, as shown in figure 2(b). Another approach to achiever SPC is to drive an impulse signal to a wavelength modulated meander-line coil and using another identical meander-line coil as the receiver, as shown in figure 2(c) [12]. When a frequency modulated signal is used to drive the wavelength modulated meander-line coil, the generated Rayleigh waves is compressed by the combination of temporal and spatial pulse compression (TSPC), as shown in figure 2(d).…”
Section: Theory Of Temporal and Spatial Pulse Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the receiver is a spatial matched filter, spatial pulse compression (SPC) can be realized, as shown in figure 2(b). Another approach to achiever SPC is to drive an impulse signal to a wavelength modulated meander-line coil and using another identical meander-line coil as the receiver, as shown in figure 2(c) [12]. When a frequency modulated signal is used to drive the wavelength modulated meander-line coil, the generated Rayleigh waves is compressed by the combination of temporal and spatial pulse compression (TSPC), as shown in figure 2(d).…”
Section: Theory Of Temporal and Spatial Pulse Compressionmentioning
confidence: 99%
“…The phase-coded coil spatial pulse compression technique was used to improve the spatial resolution and SNR of Rayleigh waves [11]. An alternative approach is to use impulse signals passing through a pair of linear or nonlinear wavelength modulated meander-line coils [12]. The final signals of Rayleigh waves can be compressed to narrow spikes by either temporal or spatial pulse compression after the processing of the received signals.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al proposed a new non-uniform coil structure for a Raleigh wave EMAT (RW-EMAT), which enables signal compression in the spatial domain. The experimental results showed an increase in received signal amplitude by 2.3–2.6 times [ 25 ]. Wang et al found that the position of the backplate affects the pulse width and amplitude of the thickness measurement signal.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research on ϕ-OTDR is mainly focused on four aspects: extending sensing distance, improving spatial resolution, expanding frequency response range, and accurately identifying disturbances [9][10][11][12]. Among these, research on improving spatial resolution mainly centers on the use of pulse compression techniques [13][14][15][16]. Research on expanding the frequency response range primarily concentrates on Frequency Division Multiplexing (FDM) [17,18], fused interferometry [19,20], and periodic non-uniform sampling [21,22].…”
Section: Introductionmentioning
confidence: 99%